Advantages of the Silkworm As an Animal Model for Developing Novel Antimicrobial Agents - Panthee, Suresh; Paudel, Atmika; Hamamoto, Hiroshi; Sekimizu, Kazuhisa (Frontiers in Microbiology, 2017)
The demand for novel antibiotics to combat the global spread of multi drug-resistant pathogens continues to grow. Pathogenic bacteria and fungi that cause fatal human infections can also kill silkworms and the infected silkworms can be cured by the same antibiotics used to treat infections in the clinic. As an invertebrate model, silkworm model is characterized by its convenience, low cost, no ethical issues. The presence of conserved immune response and similar pharmacokinetics compared to mammals makes silkworm infection model to examine the therapeutic effectiveness of antimicrobial agents. Based on this, we utilized silkworm bacterial infection model suitable to screen the therapeutic effectiveness of various microbial culture broths and successfully identified a therapeutically effective novel antibiotic, lysocin E, which has a novel mode of action of binding to menaquinone, thus leading to membrane damage and bactericidal activity. The similar approach to screen potential antibiotics resulted in the identification of other therapeutically effective novel antibiotics, such as nosokomycin and ASP2397 (VL-2397). In this regard, we propose that the silkworm antibiotic screening model is very effective for identifying novel antibiotics. In this review, we summarize the advantages of the silkworm model and propose that the utilization of silkworm infection model will facilitate the discovery of novel therapeutically effective antimicrobial agents.